Cognitive processes in autism: Repetitive thinking in autistic versus non-autistic adults. (May 2022) - Cooper, Kate; Russell, Ailsa; Calley, Steph; Chen, Huilin; Kramer, Jaxon; Verplanken, Bas
Repetitive and restricted behaviours are a core feature of autism, and cognition in autistic individuals may also be repetitive and restricted. We aimed to investigate the relationship between repetitive behaviours and repetitive thinking. We predicted that autistic people would experience more repetitive, perseverative, visual and negative cognition than controls. We predicted that repetitive thinking would be associated with repetitive behaviours in the autistic participants. We recruited autistic ( n = 54) and control ( n = 66) participants who completed measures of insistence on sameness and obsessive-compulsive behaviours. Participants then took part in 5 days of descriptive experiencing sampling, recording their thoughts when a random alarm sounded. Consistent with our hypothesis, autistic participants reported more repetitive thinking. Contrary with our other hypotheses, autistic participants reported equivalent frequency of perseveration, visual thoughts and negative thoughts to non-autistic participants. Moreover, participants who reported more obsessive thinking reported more repetitive behaviour (insistence on sameness), but there was no such relationship between repetitive thinking and behaviour. Autistic participants who reported more repeated thoughts in the descriptive experience sampling had significantly lower obsessive thinking scores. We conclude that anxiety focused cognitions may drive insistence on sameness behaviours, and that the relationship between repetitive cognition and behaviour is complex and warrants further investigation. Lay abstract: A core feature of autism is the tendency to do the same activity or behaviour repetitively. We wanted to find out if autistic people also experience repetitive thinking, for example, having the same thoughts repeatedly. We thought that there would be a link between repetitive behaviour and repetitive thinking. We asked 54 autistic people and 66 non-autistic people to complete questionnaires measuring repetitive behaviours and obsessive thinking. Next, participants were trained by a researcher to record their thoughts using a structured paper form. They then completed 5 days of thought recording, which they did each time a random alarm sounded on their mobile phone. We found that autistic people had more repetitive thoughts than non-autistic people, but they did not report having more negative or visual thoughts compared with non-autistic people. Autistic people who had more repetitive thoughts during the 5 days of thought recording did not report more repetitive behaviour. However, autistic people who reported more obsessive thinking, for example, more negative and unwanted thoughts, also reported higher levels of repetitive behaviour. We conclude that some repetitive behaviours may be linked to anxiety and that more research is needed to better understand repetitive behaviours in autism.